The Sino-Us Relations – Recalibration or Repetition? - Qi, Lin (AEI Insights, 2021)
“The Chinese grab for fossil fuels or its military competition for naval control is not a challenge but rather a boost for the US Asia-Pacific –even an overall– posture. Calibrating the contraction of its overseas projection and commitments – some would call it managing the decline of an empire – the US does not fail to note that nowadays half of the world’s merchant tonnage passes though the South China Sea. Therefore, the US will exploit any regional territorial dispute and other frictions to its own security benefit, including the costs sharing of its military presence with the local partners, as to maintain pivotal on the maritime edge of Asia that arches from the Persian Gulf to the Indian Ocean, Malacca, the South and East China Sea up to the northwest–central Pacific. Is China currently acting as a de facto fundraiser for the US?”– Professor Anis H. Bajrektarevic famously asked in his policy paper ‘What China wants for Asia: 1975 or 1908?’.